Remix New Modernities in a Post-Indian World - Baker, Joe; McMaster, Gerald (Heard Museum/Natural Museum of American Indian, 2007)
Published in conjunction with the exhibition of the same name, on view at the Heard Museum in Phoenix, Arizona, from October 6, 2007, to April 27, 2008, and at the George Gustav Heye Center, National Museum of the American Indian, in New York, New York, from May 26 through September 30, 2008
OCLC: 845281405
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé